(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2025)
Background. This study investigated the effect of 4-(1H-pyrazol-1-ylmethyl)phenylmethacrylate (m1) and 4-(1H-1,2,4-triazol-1-yl)phenylmethacrylate (m2) on the kinetics and parameters of the thermal oxidative degradation of polystyrene modified with them using dynamic thermogravimetric analysis (TGA). Methods. The synthesis of polystyrene and modified samples was carried out by the method of intra-chain doping by adding 3 mol% of monomer additives to the base monomer during its radical thermally initiated polymerization. Results. The thermal oxidation degradation behavior of the modified polystyrene samples was analyzed and compared with unmodified polystyrene synthesized under identical conditions. The comparison was aimed at evaluating how the introduction of azole-containing phenyl methacrylates affects the thermal stability of polystyrene. Using the Coates-Redfern kinetic model, the thermogravimetric analysis data were processed and the activation energy (Ea), pre-exponential factor (Z), and rate constant (k) of degradation were calculated. Сonclusions. It has been shown that the m2 monomer, when covalently introduced into the polymer, can be recommended for practical use in the manufacture of thermally stabilized polystyrene.